An Analysis of Aggression Levels among Different Combative Sports Players - Ms. Hemlata; Dr. Vishnu Chaudhari (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Objective: To compare the Aggression Levels among Different Combative sports Players. Method: The purpose of the study was to compare the selected psychological factor such as Aggression Levels among Different Combative sports Players. The study was conducted on ninety (N=90), which includes thirty each Boxing (N1=30), Wushu (N2=30) and Karate (N3=30) male national level players of age ranging from 18 to 25 years. Who were attend the national level tournaments. After reviewing through all the scientific literature, journals, magazine and keeping feasibility criteria in mind the content Aggression was selected for the purpose of the present study. Aggression was assessed by using the scale developed by Anand Kumar and Prema Shankar. In order to find-out significant difference among male National Boxing, Wushu and Karate Players on aggression level ANOVA was used. To know more about the pattern of differences existing within a set of population means, Least Significant Difference (LSD) Post-hoc test was used. The significance was tested at 0.05 level. All the statistical procedure was performed with the help of SPSS (V.19). Result: The result of the study reveals that there was a significant difference in the mean score of aggression among Selected national level Boxing, Wushu and Karate Players. The reported mean scores and standard deviation of aggression in relation to national level Boxing is 10.80 and 1.49. The mean and standard deviation of aggression in relation to national level Wushu is 10.00 and 1.28. The mean and standard deviation of aggression in relation to national level Karate is 9.43 and 1.33. Conclusion: On the basis of the analysis of the data and obtained results it was found that there was important change in players participating in different competition level in their sports aggression. The findings of the study revealed that there was a significant difference in the mean score of aggression among Selected national level Boxing, Wushu and Karate Players. It was concluded that national level Boxing players had higher level of aggression and national level Karate players had lower level of aggression among the groups. One of the main recommendations of the research is the need to focus on the psychological preparation for national level players, as well as the need for a sport psychologist to work with national teams.